Pengaruh Kegiatan Montase Terhadap Kreativitas Anak Usia 5-6 Tahun Di TK Pembina Sidikalang Kabupaten Dairi - Sriwahyuni Tarigan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine whether montage activities have an influence on improving the creativity of children aged 5–6 years at TK Negeri Pembina Sidikalang, Dairi Regency. This study employed a descriptive quantitative research method. The population consisted of all children at TK Negeri Pembina Sidikalang, totaling 223 students, and a sample of 31 children was selected using the purposive sampling technique.The instrument trial was conducted on 33 students of TK Pembina Sidikalang, Dairi District, who were not included in the research sample. The results showed that all research instruments were valid and reliable as they met the required validity and reliability criteria. Data were collected using a questionnaire consisting of 25 items, including 15 items for variable X and 10 items for variable Y.The results of the data analysis indicate that montage activities have a positive and significant effect on early childhood creativity at TK Negeri Pembina Sidikalang, Dairi Regency. This is supported by the following findings:Analysis prerequisite test:a) The correlation test obtained a value of rxy = 0.587 > rtable (α = 0.05, n = 31) = 0.355, indicating a positive relationship between variable X and variable Y.b) The significance test showed that tcount = 3.903 > ttable (α = 0.05, df = n − 2 = 29) = 2.045, indicating a significant relationship between the two variables.Effect test:a) The regression equation test produced the regression equation Ŷ = 10.667 + 0.469X.b) The coefficient of determination (r²) was 34.4%. Thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (H₀) is rejected.